2002
DOI: 10.1074/jbc.m201879200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Cation-dependent Mannose 6-Phosphate Receptor with GGA Proteins

Abstract: The GGAs (Golgi-localizing, ␥-adaptin ear homology domain, ARF-binding) are a multidomain family of proteins implicated in protein trafficking between the Golgi and endosomes. Recent evidence has established that the cation-independent (CI) and cation-dependent (CD) mannose 6-phosphate receptors (MPRs) bind specifically to the VHS domains of the GGAs through acidic cluster-dileucine motifs at the carboxyl ends of their cytoplasmic tails. However, the CD-MPR binds the VHS domains more weakly than the CI-MPR. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 27 publications
2
54
2
2
Order By: Relevance
“…This latter finding is in agreement with observations from a previous study in which clathrin expression was reduced by antisense RNA (Iversen et al, 2003). The involvement of AP1 in the sorting of cathepsin D could depend on its role in the packaging of mannose 6-phosphate receptors into clathrin-coated vesicles at the TGN (Doray et al, 2002). However, AP1 has also been proposed to be localized to endosomes (Futter et al, 1998) and to play a role in the sorting of mannose 6-phosphate receptors from endosomes to the TGN (Meyer et al, 2000).…”
Section: Requirement Of the Gak-ap1 Interaction For Lysosomal Enzyme supporting
confidence: 83%
“…This latter finding is in agreement with observations from a previous study in which clathrin expression was reduced by antisense RNA (Iversen et al, 2003). The involvement of AP1 in the sorting of cathepsin D could depend on its role in the packaging of mannose 6-phosphate receptors into clathrin-coated vesicles at the TGN (Doray et al, 2002). However, AP1 has also been proposed to be localized to endosomes (Futter et al, 1998) and to play a role in the sorting of mannose 6-phosphate receptors from endosomes to the TGN (Meyer et al, 2000).…”
Section: Requirement Of the Gak-ap1 Interaction For Lysosomal Enzyme supporting
confidence: 83%
“…This requirement for serine phosphorylation to effect autoinhibition may relate to the internal location of the AC-LL motifs of GGA1 and GGA3. We and others have shown that the binding of the MPR AC-LL motifs to the VHS domains requires a precise spacing between the dileucines and the free C terminus of the receptors (12,18). The addition of alanines to the MPR C terminus greatly inhibited binding to the VHS domain.…”
Section: Discussionmentioning
confidence: 99%
“…2D). Furthermore, depletion of GAK had a marked effect on trafficking of MPR from the TGN to the lysosome, which normally occurs via vesicles containing clathrin, GGA and AP1 (Doray et al, 2002). Most of the MPR is distributed throughout the cytosol in the knockdown cells, whereas it is present at the TGN in mockdepleted cells (Fig.…”
Section: Functional Changes In Gak-depleted Cellsmentioning
confidence: 99%